Flotation of Chromium Ions from Simulated Wastewater Using Air Microbubbles - Abd Alhuseen, Hayder Noori; Abdulrazzaq, Nada N.; Sedev, Rossen (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
A microbubble air flotation technique was used to remove chromium ions from simulated wastewater (e.g. water used for electroplating, textiles, paints and pigments, and tanning leather). Experimental parameters were investigated to analyze the flotation process and determine the removal efficiency. These parameters included the location of the sampling port from the bottom of the column, where the diffuser is located to the top of flotation column (30, 60, and 90 cm), the type of surfactant (anionic, SDS, or cationic, CTAB) and its concentration (5, 10, 15, and 20 mg/L), the pH of the initial solution (3, 5, 7, 9, and 11), the initial contaminant concentration (10, 20, 30, and 40 mg/L), the gas flow rate (0.1, 0.2, 0.3, and 0.5 L/min), and the contact time (5, 10, 15, 20, 25, 30, and 35 min). The experimental results revealed that the highest removal efficiency (95%) was achieved in 20 min with a pH of 7, a flow rate of air 0.5 L/min, an SDS surfactant concentration of 15 mg/L, and a pollutant concentration of 30 mg/L at a sampling port height of 30 cm. The use of microbubbles in comparison to normal bubbles, resulted in a 56% improvement of the removal efficiency. The flotation process follows a first-order kinetics.